2015
DOI: 10.1016/j.jmhi.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Induction of spontaneous neo-angiogenesis and tube formation in human endometrial stem cells by bioglass

Abstract: Endothelial dysfunction is a broad pathological disorder of the endothelium (innermost layer of blood vessels) which is assigned by vasoconstriction, thrombosis and ischemic diseases, alone or with other disorders such as coronary artery disease, hypertension and atherosclerosis. The fundamental imperfection of endothelial layer injury due to decrease in the number of functional endothelial progenitor cells and inhibition of endothelial progenitor cell differentiation, resulting into impairment of angiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“… Chan et al (2004) also confirmed the presence of clonogenic stem cell populations in the endometrium tissue ( Chan et al, 2004 ). We already proved that this mentioned regenerative capacity in the endometrium tissue is due to the presence of EnSCs that were demonstrated to be immuno-privileged in comparison with other cell types ( Shamosi et al, 2015 ), shedding new light on cell-based therapies and rendering these cells a promising resource in limb tissue regeneration ( Figure 3 ). The human endometrium is a highly regenerative tissue due to the fact that a complete regeneration of the uterus can be achieved after almost total resection of the endometrium, with the renovated endometrium still maintaining its ability to support gestation ( Murphy et al, 2008 ).…”
Section: Endometrial-derived Stem Cells: All-in-one For Limb Regenera...mentioning
confidence: 93%
See 1 more Smart Citation
“… Chan et al (2004) also confirmed the presence of clonogenic stem cell populations in the endometrium tissue ( Chan et al, 2004 ). We already proved that this mentioned regenerative capacity in the endometrium tissue is due to the presence of EnSCs that were demonstrated to be immuno-privileged in comparison with other cell types ( Shamosi et al, 2015 ), shedding new light on cell-based therapies and rendering these cells a promising resource in limb tissue regeneration ( Figure 3 ). The human endometrium is a highly regenerative tissue due to the fact that a complete regeneration of the uterus can be achieved after almost total resection of the endometrium, with the renovated endometrium still maintaining its ability to support gestation ( Murphy et al, 2008 ).…”
Section: Endometrial-derived Stem Cells: All-in-one For Limb Regenera...mentioning
confidence: 93%
“…This therapeutic response is triggered through the stem cell differentiation to endothelial cells and secreting various types of pro-angiogenic factors into the injured tissue microenvironment ( Khodayari et al, 2019 ). Based on experimental observations, the MSCs, EPCs, and EnSCs are the cells that show both the responses after transplantation ( Shamosi et al, 2015 ; Bouland et al, 2021 ), while the MNCs have no significant differentiation potential, and it seems their efficacy is induced via regulating the ischemic tissue environment ( Li et al, 2006 ). These facts raise the possibility that releasing pro-angiogenic factors can be the main factor for inducing therapeutic angiogenesis into the injured limb.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that supernatant of cultures on Gel/Col/BG scaffold contained significantly higher amounts of VEGF compared to culture son Gel/Col scaffold (2.14 folds, P<0.001). This finding indicates that BG inclusion in hydrogel scaffold triggers expression of VEGF and subsequently promotes angiogenesis [30].…”
Section: Vegf Secretion Levels By Cells On Scaffoldsmentioning
confidence: 93%
“…[24,28,32] These unique features (e.g., biodegradability, biocompatibility, drugdelivery, osteogenic, and angiogenic potential) make MBGs desirable candidates for biomedical applications including cancer therapy. [41,52,53] In recent years, many preclinical studies have developed stable MBGs with controlled delivery of drugs, desirable biosafety, and efficient suppression of tumor growth to pave the way for clinical applications. [34,[54][55][56] Besides MBG applications in different cancer types, special consideration has been devoted to bone cancer rooting in the therapeutic/regenerative effects of released ions (Si, Ca, and P) from the MBGs' structure.…”
Section: The Significance Of Mbgs: Overview On the Role Of Cancer Tre...mentioning
confidence: 99%
“…[ 24,28,32 ] These unique features (e.g., biodegradability, biocompatibility, drug‐delivery, osteogenic, and angiogenic potential) make MBGs desirable candidates for biomedical applications including cancer therapy. [ 41,52,53 ] In recent years, many preclinical studies have developed stable MBGs with controlled delivery of drugs, desirable biosafety, and efficient suppression of tumor growth to pave the way for clinical applications. [ 34,54–56 ]…”
Section: The Significance Of Mbgs: Overview On the Role Of Cancer Tre...mentioning
confidence: 99%